Novel Regulation of Calcium Inhibition of the Inositol 1,4,5-trisphosphate Receptor Calcium-release Channel - Mak, Don-On Daniel (The Rockefeller University Press, 2003)
The inositol 1,4,5-trisphosphate (InsP(3)) receptor (InsP(3)R), a Ca(2+)-release channel localized to the endoplasmic reticulum, plays a critical role in generating complex cytoplasmic Ca(2+) signals in many cell types. Three InsP(3)R isoforms are expressed in different subcellular locations, at variable relative levels with heteromultimer formation in different cell types. A proposed reason for this diversity of InsP(3)R expression is that the isoforms are differentially inhibited by high cytoplasmic free Ca(2+) concentrations ([Ca(2+)](i)), possibly due to their different interactions with calmodulin. Here, we have investigated the possible roles of calmodulin and bath [Ca(2+)] in mediating high [Ca(2+)](i) inhibition of InsP(3)R gating by studying single endogenous type 1 InsP(3)R channels through patch clamp electrophysiology of the outer membrane of isolated Xenopus oocyte nuclei. Neither high concentrations of a calmodulin antagonist nor overexpression of a dominant-negative Ca(2+)-insensitive mutant calmodulin affected inhibition of gating by high [Ca(2+)](i). However, a novel, calmodulin-independent regulation of [Ca(2+)](i) inhibition of gating was revealed: whereas channels recorded from nuclei kept in the regular bathing solution with [Ca(2+)] ∼400 nM were inhibited by 290 μM [Ca(2+)](i), exposure of the isolated nuclei to a bath solution with ultra-low [Ca(2+)] (<5 nM, for ∼300 s) before the patch-clamp experiments reversibly relieved Ca(2+) inhibition, with channel activities observed in [Ca(2+)](i) up to 1.5 mM. Although InsP(3) activates gating by relieving high [Ca(2+)](i) inhibition, it was nevertheless still required to activate channels that lacked high [Ca(2+)](i) inhibition. Our observations suggest that high [Ca(2+)](i) inhibition of InsP(3)R channel gating is not regulated by calmodulin, whereas it can be disrupted by environmental conditions experienced by the channel, raising the possibility that presence or absence of high [Ca(2+)](i) inhibition may not be an immutable property of different InsP(3)R isoforms. Furthermore, these observations support an allosteric model in which Ca(2+) inhibition of the InsP(3)R is mediated by two Ca(2+) binding sites, only one of which is sensitive to InsP(3).